Research on Grid Scheduling of Super-Peer Model Based on QoS - Shanliang Pan; Xi Huang; Qinjiao Mao (Dianxin kexue)
Firstly，a kind of grid resource management model——super-peer model was proposed.For this model，economic mechanism was introduced，allowing a grid user to put forward the task’s expected execution deadline，cost limit and the weight parameters between them.Those are the QoS parameters of application-level.Then，a corresponding resource scheduling algorithm was shown.Next，hierarchical colored Petri net and price timed Petri net were used to model and the dynamic process of grid resource scheduling was simulated.Lastly，reachable task graph（RTG）of Petri net model was constructed and the system’s scheduling performance was analyzed，such as throughout capacity，load-balancing，scheduling time and cost through an example.